Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Work Life Balance Terhadap Turnover Intention (Studi Kasus pada Karyawan PT. Kanvill Berkah Abadi) - Ghomam, Muhammad Shoikhul; Wahono, Budi; Mawardi, M Cholid (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of leadership style, work environment, and work-life balance on turnover intention among employees of PT. Kanvill Berkah Abadi. Data was collected through a questionnaire survey filled out by 68 employees. The data analysis used multiple linear regression. The results of the study show that leadership style, work environment, and work-life balance have a significant influence on turnover intention. Leadership style and work environment negatively influence turnover intention, while work-life balance has a positive effect. The study concludes by emphasizing the importance of effective leadership, creating a conducive work environment, and maintaining a balance between work and personal life to reduce turnover intention. Keyword:  Leadership Style, Work Environment, Work Life Balance, Turnover Intention.